Northern News - North America, Arctic Institute of (ARCTIC, 1953)
The news items include: 1) an report on the first meeting of the committee appointed at the Canadian Eskimo Conference (reprinted from Arctic Circular, v. 5, no. 6, 1952, p. 63-64); 2) information from J. Brian Bird on the etymology of the name "walrus"; 3) information about the new series "Anthropological Papers of the University of Alaska" and a listing of papers in the first volume; 4) a request from Evelyn Stefansson who wants to know whether any copies of the Russian periodical "Letopis' Severa" made it to North America; and 5) a translation of S.L. Markov's account of the "The discovery of ancient coins in the Kamchatka" by Evelyn Stefanson.